Riesgo de desarrollar diabetes mellitus tipo 2 en la población de la cabecera cantonal de Yacuambi - Torres Aguilar, Lisseth Alexandra (2021)
Type 2 diabetes mellitus is a public health problem associated with risk factors and characterized by an alteration in carbohydrate metabolism. The present study aimed to establish the risk of developing type 2 diabetes mellitus; identify the level of education, economic activity and cigarette consumption as associated factors; develop health promotion and prevention actions in the cantonal head of Yacuambi. A mixed, cross-sectional cohort approach was applied through a field investigation with a sample of 246 people. To whom a structured survey and the FINDRISC test were applied. Obtaining the following results: most of the population has a low risk of developing DM2 with 51,60%, the factors associated with developing type 2 diabetes mellitus are female with 10,6%; the age group <45 with 7,4%; the level of primary and secondary education with 7.1% respectively; work activities, household chores and personal services with 14,5%, the factor that doesn´t influence is cigarette consumption. Determining in the population, with the FINDRISC test, moderate, high and very high risk with 6.1%, 3.3% and 0.0% respectively; to present DM2 in the next 10 years. Keywords: Findrisc test, risk factors, body mass, educational level.